International Enrollments in the United States: 60 Years of 'Open Doors' Data - Chow, Patricia; Chambers, Julie (International Higher Education, 2010)
When IIE started to report the census on international students at colleges or universities in the United States in 1948/49, only 25,464 international students were reported. In 2008/09, the number was 671,616, which was itself an 8% increase from the previous year. As for the trends by sending regions, 62% of international students were from Asia in 2008/09, though it was 26% in 1948/49; this outnumbered the modest increase of students from Europe and Latin America during the period. Recently, graduate international students outnumbered undergraduate international students.